2019
DOI: 10.1123/wspaj.2019-0030
|View full text |Cite
|
Sign up to set email alerts
|

Final Thoughts on Women in Sport Coaching: Fighting the War

Abstract: This collection of articles about and for women in sport coaching provides more evidence of the occupational landscape and experiences of women. As with countless empirical articles before, the eight articles in this special issue of Women in Sport and Physical Activity Journal (WSPAJ) further uncover and reveal that structural-level systemic bias is deeply embedded within the culture of sport-the data tell the story. With more data, the story plotline becomes sharply focused and illuminates the many obstacles… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
47
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(64 citation statements)
references
References 19 publications
2
47
0
4
Order By: Relevance
“…Furthermore, it could be suggested that research such as ours and others (e.g. LaVoi et al, 2019: Lewis et al, 2018Clarkson et al, 2019) indicate that the FA suffers from systematic and cultural sexism and that the way their coach education courses operate are indicative of ingrained institutional practices and not the causes of them. It must be difficult for female coach-learners to be secure in the value afforded to them when, in walking the corridors of the National Centre, the vast majority of women they see are deployed in service roles, in the restaurant, behind the bar or in the administrative systems.…”
Section: Resultsmentioning
confidence: 83%
“…Furthermore, it could be suggested that research such as ours and others (e.g. LaVoi et al, 2019: Lewis et al, 2018Clarkson et al, 2019) indicate that the FA suffers from systematic and cultural sexism and that the way their coach education courses operate are indicative of ingrained institutional practices and not the causes of them. It must be difficult for female coach-learners to be secure in the value afforded to them when, in walking the corridors of the National Centre, the vast majority of women they see are deployed in service roles, in the restaurant, behind the bar or in the administrative systems.…”
Section: Resultsmentioning
confidence: 83%
“…LaVoi (2016a) defined four levels to the EIM, from the micro (agency) level of individual and intrapersonal issues, through to the macro (structural) level issues that cover organizational and sociocultural contexts. In doing so, the EIM offers explanatory value in recognizing the variables which women coaches themselves have the capacity to control, but also the organizational systems and sociocultural contexts to which they are bound (LaVoi, McGarry & Fisher, 2019). Without having applied LaVoi's (2016a) EIM model, extant literature has reported on several restrictive processes at all levels and have thus detailed how these "different levels are intertwined and influence each other bi-directionally" (LaVoi et al, 2019, p. 137).…”
Section: Under-representation Of Women Sports Coaches: a Review Of LImentioning
confidence: 99%
“…Nevertheless, the knowledge that there would be an under-presentation of women attending the courses did induce some form of anxiety even before the courses began and was acknowledged to be a barrier. This is where 'blame the women' narratives have traditionally arisen (Clarkson et al, 2019;Fielding-Lloyd & Meân, 2011;Kane & LaVoi, 2018;LaVoi et al, 2019) whereby it is women's own fault at an agential (micro) level for not having the desire and confidence to apply for jobs or attend necessary coach qualification courses.…”
Section: Formal Coach Education: a Space To Accumulate Capitalmentioning
confidence: 99%
“…There is clear underrepresentation of females in community coaching ranks as illustrated in the latest available data from Western, club-based sports systems in the UK, Canada, Australia and New Zealand. Research on the topic of female sport coaches has grown, especially over the last decade, as sport governing bodies and policy makers seek to address the lack of representation of females in coaching roles (LaVoi, et al, 2019). However, the majority of research in this area focuses on females in paid coaching roles at sub-elite or elite levels, using participants who are current or former professional level coaches within the American National Collegiate Athletic Association (NCAA), Canadian USport, and various national sport systems (e.g., Bruening & Dixon, 2008;Dixon & Sagas, 2007).…”
Section: Introductionmentioning
confidence: 99%